Analisis Molekuler Resistensi terhadap Pasien dengan Multidrug Resistance Tuberculosis (MDR TB) - Aliya Rifani; Cynthia Irene Zhu; M. Revo Artmando Lindani (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Mycobacterium tuberculosis is a bacterium that causes tuberculosis disease, which in the healing process requires a long time because this bacterium has a resting phase or what is called a dormant phase. This is one of the factors that cause patients who are undergoing tuberculosis treatment to experience saturation and stop treatment before the specified time. Resistance to antituberculosis drugs is a result of negligence in treatment so that bacteria become resistant to several types of antituberculosis drugs called multidrug resistance tuberculosis (MDR TB). This systematic review aims to examine the molecular structure of Mycobacterium tuberculosis bacteria and its correlation with the mechanism of resistance to antituberculosis drugs, especially Isoniazid and Rifampicin..